Karakteristik Habitat Dan Populasi Tarsius (Tarsius dentatus) Di Resort Ii Baturube Kawasan Cagar Alam Morowali Kabupaten Morowali Utara - Ella Krisnatalya; Sri Ningsih Mallombasang; Yulius Duma (Universitas Tadulako, 2020)
Tarsius is one of the endemic species of Sulawesi found in various habitat types, namely primary forest, secondary forest and transition secondary forest. This study aims to observe habitat characteristics and estimate the population density of tarsiers (Tarsius dentatus) at Resort II Baturube Morowali Nature Reserve area, North Morowali District. Observation of habitat characteristics uses a Porposive sampling by using the plot line method and estimation of population density using thepoint count method. The results of studies showed that the tarsier habitat began at a height of 312-163 masl with slopes of 4-25%. Habitat temperature ranges from 20.3˚C-29.5˚C and air humidity ranges from 80% -98% while the light intensity that enters the tarsier habitat ranges from 200-3500 lux. Retrieval of data on vegetation components found that tarsier habitats many occupy bamboo and ficus sp. The highest important value index for the three types of tarsier habitat at the tree level is Ficus insipida (Moraceae) (98.36), pole level Pseudolmedia sp (Moraceae) (107.2), sapling level Protium sp (2) (Burseraceae) (70.8), and seedling levelPandanus sp (2) (Pandanaceae) (91.01). The highest Tarsier population density was found in transition secondary forest habitats with a population density of 2.17 individuals / ha, in secondary forests of 1.95 individuals /ha and in primary forests of 1.17 individuals / ha.